MEDIA CASE-BASED LEARNING TO BUILD PEACE-LOVING CHARACTER IN STUDENTS PGSD STUDY PROGRAM - Arif Firmansyah; Nur Rahmah; Jeisi Riska Merdekawati Mentu (Jurnal Dikdas, 2022)
This type of descriptive research is quantative with survey methods. The number of research samples as many as 103 students determined based on the calculation of samples according to Arikunto. Sampling techniques using purposive proportional random sampling consisting of students semester VI. Data collection is done by questionnaires, interviews, observations and documentation. Quantitative data analysis is presented in the categories "good" (x>75.00), "sufficient" (60.00<x<75.00), "less" (x<56.00). Qualitative data in the form of discourse and implementation of selected character education values are analyzed and interpreted in descriptive form. The results showed that in planning lecturers have made learning programs in the form of habituation and academic culture related to the values of love peace characters. The implementation of campus programs in the form of habituation and academic culture related to the value of hard work, discipline and love of peace is by 1) Holding and maximizing facilities supporting hard work e.g. doing tasks; 2) Make lecture contracts for students who program courses to train student disciplines; 3) Maximizing the function of the box of discovery of goods in practicing the attitude of peace-loving students, so that the character of peace-loving in the pattern of campus association. Based on the results of the poll most students showed the value of hard work is "enough" (71.77%), the value of discipline is "sufficient" (74.79%), the value of peace is "enough" (73.69%). Of the three values, the value of hard work is the lowest percentage of 71.77%, while the value of the three indicators of character love peace is 73.56% of the category is sufficient. Therefore, efforts are needed to increase the value of love peace characters in the PGSD FKIP Untad study program.